Sintering behaviour and dielectric properties of BaTiO3: Effect of borax addition - Othman Kolthoum I.; Ali Mostafa El Sayed; El-Houte Samia Imam (Processing and Application of Ceramics)
Barium titanate (BaTiO3) is a prominent ferroelectric material widely utilized in various electronic applications, due to its excellent dielectric properties. Lowering its sintering temperature, a highly demanded requirement in multilayer ceramic capacitors (MLCC), enables the use of metal-based electrodes and consequently reduces the production cost. In the present work, we investigated the impact of using low melting glassy phases of borax (Na2B4O7 • 10H2O) in developing low-temperature-sintered BaTiO3 ceramics. The effects of borax addition on the densification, microstructure and dielectric properties of BaTiO3 ceramics were investigated. Different amounts of borax were added to BaTiO3 powders, and the compacts made from these mixtures were sintered at 1100 and 1150°C for 3 h. The results revealed that this small addition of borax can effectively reduce the sintering temperature of BaTiO3 to 1100°C. The presence of the borax liquid phase at the BaTiO3 grain boundaries enhanced densification at such low temperature, without formation of secondary phases or degradation of the dielectric properties. Relative permittivities up to 2410 and 7685 at room and Curie temperatures, respectively, were obtained.